TWO POLES OF LITERARY ADAPTATION TO INDONESIAN FILMS: A CASE STUDY OF MEREKA BILANG, SAYA MONYET! AND DILAN 1990 - Suseno Suseno; Agus Nuryatin; Teguh Supriyanto; Mukh Doyin (INDONESIA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2026)
This study aims to analyse and compare the adaptation style in films, Mereka Bilang, Saya Monyet!  and Dilan 1990. A qualitative method with a comparative descriptive approach is used. Data were collected through literature studies and audiovisual analysis, then analysed with a focus on adaptation strategies, visual styles, and production orientation. The result, Mereka Bilang, Saya Monyet! Applying an interpretive-expressive style that transforms fragmentary texts into cinematic explorations based on social and psychological criticism. In contrast, Dilan 1990 uses direct transposition with high fidelity to the source novel to meet the expectations of a mass audience. In conclusion, the choice of adaptation style is a complex decision determined by the characteristics of the literary text, the production objectives, and the target audience.